Safeguarding vitality and cognition: The role of sarcopenia in intrinsic capacity decline among octogenarians from multiple cohorts - Pi-Shan Hsu; Wei-Ju Lee; Li-Ning Peng; Wan-Hsuan Lu; Lin-Chieh Meng; Fei-Yuan Hsiao; Liang-Kung Chen (Elsevier, 2024)
Background: Sarcopenia and intrinsic capacity (IC) declines pose significant challenges to healthy aging, particularly in the rapidly growing octogenarian population. This study aimed to elucidate the relationship between sarcopenia and declines in IC across multiple cohorts of community-dwelling older adults. Methods: Data from four Taiwanese cohorts were analyzed. Sarcopenia was diagnosed based on the Asian Working Group for Sarcopenia (AWGS) 2019 criteria (algorithm 1: categorized as either having possible sarcopenia or not (robust); algorithm 2: categorized as robust, possible sarcopenia or sarcopenia). IC was operationalized using the World Health Organization's Integrated Care for Older People (ICOPE) framework (step 1 and step 2), encompassing six domains: locomotion, vitality, vision, hearing, cognition, and psychological well-being. Multivariable logistic regression models were adopted to assess the association between sarcopenia and IC decline. Results: Among 599 octogenarians (median age 82.2 years, 54.8% male), the prevalence of possible sarcopenia (algorithm 1) was 64.6%. When adopting algorithm 2, the prevalence of possible sarcopenia and sarcopenia was 46,2% and 32.1%, respectively. After adjusting for covariates, participants with possible sarcopenia or sarcopenia (algorithm 2) were more likely to exhibit declines in vitality (ICOPE Step 1: possible sarcopenia aOR 3.65, sarcopenia aOR 4.74; ICOPE Step 2: possible sarcopenia aOR 5.11, sarcopenia aOR 14.77) and cognition (ICOPE Step 1: possible sarcopenia aOR 2.40, sarcopenia aOR 2.12; ICOPE Step 2: possible sarcopenia aOR 2.02, sarcopenia aOR 2.51) compared to robust individuals. Conclusions: This study underscores the robust association between sarcopenia and declines in vitality and cognition among octogenarians, highlighting the importance of sarcopenia screening and management in promoting healthy longevity in this vulnerable population.